Seasonal and spatial variability of selected surface water quality parameters in Setiu Wetland, Terengganu, Malaysia - S. Suratman,; A.N.A.R. Hussein,; N. Mohd Tahir,; M.T. Latif,; R. Mostapa,; K. Weston, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This paper presents the results for surface water quality parameters measured in the Setiu Wetland, on the east coast of Malaysia, which feeds into the southern part of the South China Sea. There are no previous studies dealing with the seasonal and spatial variation of water quality in this area, despite numerous anthropogenic inputs into this ecologically and economically important wetland. The parameters measured were salinity, temperature, dissolved oxygen (DO), pH, biological oxygen demand (BOD) and total suspended solids (TSS). These parameters were sampled monthly from October 2009 to September 2010, during both the wet and dry seasons, at ten sampling stations distributed throughout the area. The physical water quality parameters were measured in situ whilst TSS and BOD were determined using the standard methods. A deterioration of water quality in the Setiu Wetland was observed in areas near agriculture and aquaculture activities. This was expected to be as a result of the use of fertilisers, waste from fish farm food and the waste products of aquaculture. The parameters measured showed lower mean values of surface salinity, temperature, DO, pH and TSS during the wet season relative to the dry season. In contrast, the concentration of BOD was high during the wet season and lowest in the dry season. Results obtained from this study clearly showed the surface physical water quality for the Setiu Wetland was highly influenced by anthropogenic activities and seasonal variation. Therefore, both factors must be considered to move towards proper management of this wetland.